2019
DOI: 10.1292/jvms.19-0197
|View full text |Cite
|
Sign up to set email alerts
|

ATP-dependent potassium channels contribute to motor regulation of esophageal striated muscle in rats

Abstract: The aim of the present study was to clarify roles of ATP-dependent potassium channels (KATP channels) in motility of the striated muscle portion in the esophagus. An isolated segment of the rat esophagus was placed in an organ bath and mechanical responses were recorded using a force transducer. Electrical stimulation of the vagus nerve evoked contractile response of striated muscle in the esophageal segment. Application of glibenclamide, an antagonist of KATP channels, increased amplitude of vagally mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…On the basis of the findings presented here, we consider that P2Y receptors and K ATP channels are localized on smooth muscle cells of muscularis mucosae and are involved in the regulation of esophageal motility. In accordance with this, we have shown localization of K ATP channels on smooth muscle cells of muscularis mucosae of rat esophagi [ 55 , 56 ]. However, it should be noted that P2Y receptors might be located on interstitial cells of Cajal (ICCs).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…On the basis of the findings presented here, we consider that P2Y receptors and K ATP channels are localized on smooth muscle cells of muscularis mucosae and are involved in the regulation of esophageal motility. In accordance with this, we have shown localization of K ATP channels on smooth muscle cells of muscularis mucosae of rat esophagi [ 55 , 56 ]. However, it should be noted that P2Y receptors might be located on interstitial cells of Cajal (ICCs).…”
Section: Discussionsupporting
confidence: 70%
“…In accordance with this, nicorandil, an agonist of K ATP channels, causes relaxation of smooth muscle in the lower esophageal sphincter of the rat [ 58 ]. We previously demonstrated that K ATP channels also contribute to motor regulation of striated muscle in the rat esophagus [ 55 , 56 ]. We think that elucidation of the coordination between striated muscle and smooth muscle is an important issue in studies on esophageal motor regulation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 ] Moreover, a dose-dependent inhibition of smooth muscle contraction by K ATP channel activators such as minoxidil, cromakalim, and diazoxide has been demonstrated in the stomach and other regions of the GI tract, including the esophagus, ileum, and colon. [ 19 20 ] The activation of K ATP channel increases potassium conductance, leading to cell membrane hyperpolarization and subsequent inhibition of extracellular Ca 2+ influx and Ca 2+ release from intracellular storage organelles. [ 21 ] Studies have also demonstrated that K ATP channel opener-induced hyperpolarization is responsible for its relaxing action on ACh- and KCl-induced contractions in the smooth muscle of rat and the gastric antrum of guinea pig.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Horii et al . [ 19 ] showed a dose-dependent effect of glibenclamide on esophagus muscle contractions in rat. In this study, glibenclamide increased vagally induced contractions of the rat esophagus at an effective dose of more than 500 μM, while glibenclamide at a dose of 50 μM did not affect esophageal muscle motility.…”
Section: Discussionmentioning
confidence: 99%
“…It helps regulate fluid balance, nerve signals and muscle contractions and beneficial aspects include reduction in blood pressure, water retention; prevention of kidney stones, osteoporosis, and protection against strokes. It functions to maintain intracellular osmotic known to play a role in Na + -K+ ATPase for effective muscle contraction [40] and motor regulation is by ATP driven potassium channels [41]. ATP driven potassium channel deficiency affected resting tension of skeletal muscle [42] deficiency of potassium ions alters sodium potassium pump of skeletal muscle and augments its contraction in ageing [43].…”
Section: Potassium (K)mentioning
confidence: 99%